GRINDING IMIDATION OF ANHYDRIDES ON SMECTITE CLAYS AS RECYCLABLE AND HETEROGENEOUS CATALYSTS UNDER SOLVENT-FREE CONDITIONS - Marvi, Omid (Journal of the Chilean Chemical Society, 2017)
Imidation of various anhydrides employing solvent-free grindstone technique using smectite clays as recyclable and green catalysts was examined and obtained excellent yields.